Karakter Morfologi Laba-laba yang Ditemukan di Area Hutan Bukit Tanjung Datok Kabupaten Sambas - Ari Hepi Yanti, Muhammad Gagit Syafriansyah, Tri Rima Setyawati (Universitas Tanjungpura, 2016)
Spiders are members of the Arachnid Class that is adaptable to the various types of habitat. This study aims to identify the morphological characters of spiders in Hutan Bukit Tanjung Datok area. Samples were taken in September 2015 by using exploring method at four cardinal directions. Spiders were found at the study site as many as twenty seven specieses belonging to the thirteen families that are Agelenidae, Araneidae, Dictynidae,Linyphiidae, Liocranidae, Lycosidae, Pholcidae, Philodromidae, Salticidae, Sparassidae, Tetragnathidae, Theridiidae, and Zodariidae. Spiders body in the Hutan Bukit Tanjung Datok had varied colour, yet dominated by the spiders in brown and black. The spiders have six to eight eyes which arranged into two rows except Lycosidae and Salticidae with three rows eye arrangement, Pholcidae whose eyes only arranged in two triads.The shape of prosoma carapace is rounded, elongated and widened. Prosoma length measured ranged from 0.7 to 25.4 mm, 0.7 to 27.3 mm in width, ophistosoma length ranged from 0.9 to 28.7 mm and 0.5 to 21.6 mm in width.